Polyimide for Electronic and Electrical Engineering Applications 2021
DOI: 10.5772/intechopen.92260
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Polyimide Dielectric Materials for Energy Storage

Abstract: The availability of high-temperature dielectrics is key to develop advanced electronics and power systems that operate under extreme environmental conditions. In the past few years, many improvements have been made and many exciting developments have taken place. However, currently available candidate materials and methods still do not meet the applicable standards. Polyimide (PI) was found to be the preferred choice for high-temperature dielectric films development due to its thermal stability, dielectric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This is because the amorphous region in the polymer blend is formed by the mixing of amorphous PVDF and PI molecular chains. [10][11][12]24 The diffraction peaks of BT appeared in the nanocomposite films in the range of tested angles, and their peak intensities increased with an increase in the proportion of PVDF in the blend. This indicates that BT@ SiO 2 is fairly equally disseminated throughout the PVDF−PI matrix to form good nanocomposite films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is because the amorphous region in the polymer blend is formed by the mixing of amorphous PVDF and PI molecular chains. [10][11][12]24 The diffraction peaks of BT appeared in the nanocomposite films in the range of tested angles, and their peak intensities increased with an increase in the proportion of PVDF in the blend. This indicates that BT@ SiO 2 is fairly equally disseminated throughout the PVDF−PI matrix to form good nanocomposite films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Intrinsically porous PIs are a kind of inherently porous material that rely solely on the polymerization of special chemical groups in monomers. As such, Shahram et al 188 prepared nanoscale PI foams with pore sizes ranging from 5 to 20 nm using PMDA and common diamines as polymeric monomers. It was demonstrated that the permittivity of the nanoscale PI foams ranged from 2.46 to 2.73 and remained stable at 370 °C.…”
Section: Intrinsically Induced Porousmentioning
confidence: 99%
“…Although intrinsically porous PIs have been studied extensively in the field of gas separation and absorption, there are few reports in the field of low- k . The fundamental reason is that the construction of intrinsically porous PI depends on monomers with rigid and distorted molecular structures (like spirobiindane (SBI), triptycene (TriP), and spirobifluorene (SBF)), so the selection of monomers is more demanding. Additionally, the monomer preparation process is laborious and time-consuming.…”
Section: Construction Of Porous Structuresmentioning
confidence: 99%
“…For instance, organic-inorganic nanocomposites exhibited hybrid properties to be used in conducting materials, optical waveguides, and photoelectronic devices (Tommalieh et al 2011;Seo et al 2020;Jeon and Baek 2010;Sanchez et al 2005). Thanks to their excellent thermal stability dielectric, and mechanical properties, polyimides have known as high-temperature polymers that are used for optoelectronic applications (Tsai et al 2016;Wu et al 2017;Zha et al 2020). The transparency of polyimide-silica thin films becomes more perspicuity through enhancing the interaction between the inorganic network and the organic moiety utilizing certain coupling agents of different molecular weights.…”
Section: Introductionmentioning
confidence: 99%